PELATIHAN TARI NYAI CUKIN BERBASIS AKULTURASI BUDAYA PERANAKAN TIONGHOA BAGI MAHASISWA CINA DI HEBEI INTERNASIONAL STUDIES UNIVERSITY - B Kristiono Soewardjo (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract This Community Service Program aims to introduce Betawi arts and culture, rooted in the acculturation of Chinese Peranakan culture, through the Nyai Cukin dance training. In addition, the program seeks to promote cultural collaboration between Hebei International Studies University (HISU) and Universitas Negeri Jakarta (UNJ). HISU, as a partner of UNJ located in Shijiazhuang, Hebei Province, has more than 21,000 students and 1,358 faculty members and staff, including foreign academics and experts. HISU has grown into a comprehensive and internationally oriented university, and is the only independent international language university at the undergraduate level in Hebei Province. HISU students are required to take Indonesian as a Foreign Language (BIPA) courses from the first to the final semester, with an emphasis on introducing Indonesian culture as part of the curriculum. The Nyai Cukin dance training, which reflects the cultural fusion of Chinese Peranakan influence, employs demonstration and imitation teaching methods. These methods are designed to facilitate students' understanding of the dance movements. The training is conducted both online and in person, covering the history of the dance, performance videos, and instructional videos. This approach greatly assists HISU students in learning and mastering the Nyai Cukin dance, enabling them to successfully perform it in front of new students. Keywords: Dance Training, Nyai Cukin Dance, Peranakan Chinese Culture Abstrak Program Pengabdian kepada Masyarakat ini bertujuan memperkenalkan seni budaya Betawi yang berlandaskan akulturasi budaya peranakan Tionghoa melalui pelatihan tari Nyai Cukin. Selain itu, program ini juga bertujuan mendorong kolaborasi budaya antara Hebei International Studies University (HISU) dan Universitas Negeri Jakarta (UNJ). HISU, sebagai mitra UNJ yang berlokasi di Shijiazhuang, Provinsi Hebei, memiliki lebih dari 21.000 mahasiswa dan 1.358 dosen serta staf, termasuk akademisi dan ahli asing. HISU telah tumbuh menjadi universitas yang komprehensif dan berskala internasional, serta merupakan satu-satunya universitas bahasa internasional mandiri di Provinsi Hebei. Mahasiswa HISU diwajibkan mengambil mata kuliah Bahasa Indonesia Penutur Asing (BIPA) dari semester awal hingga semester akhir, dengan fokus juga pada pengenalan budaya Indonesia dalam kurikulumnya. Pelatihan tari Nyai Cukin, yang mencerminkan akulturasi budaya peranakan Tionghoa, menggunakan metode pembelajaran demonstrasi dan imitasi. Metode ini dirancang untuk memudahkan mahasiswa dalam memahami gerakan tari. Pelatihan dilakukan baik secara daring maupun tatap muka, dengan menyajikan sejarah tari, video pertunjukan, serta video pembelajaran. Pendekatan ini sangat membantu mahasiswa HISU dalam mempelajari dan menguasai tari Nyai Cukin, sehingga mereka berhasil menampilkan tarian tersebut di depan mahasiswa baru dengan baik. Kata Kunci: Pelatihan Tari, Tari Nyai Cukin, Budaya Peranakan Tionghoa